Zadacha Kuznecov Predely 10-11

Материал из PlusPi
Перейти к: навигация, поиск

Условие задачи

Вычислить предел функции:

<math> \lim_{x\to 1} \frac{\sqrt[3]{x}-1}{\sqrt {1+x} -\sqrt {2x}}</math>

Решение

<math> \lim_{x\to 1} \frac{\sqrt[3]{x}-1}{\sqrt {1+x} -\sqrt {2x}} = \left\{\frac{0}{0}\right\} = \lim_{x\to 1} \frac{\left(\sqrt[3]{x}-1\right)\left(\sqrt {1+x} +\sqrt {2x}\right)}{\left(\sqrt {1+x} -\sqrt {2x}\right)\left(\sqrt {1+x} +\sqrt {2x}\right)} =</math>
<math> = \lim_{x\to 1} \frac{\left(\sqrt[3]{x}-1\right)\left(\sqrt {1+x} +\sqrt {2x}\right)}{1+x -2x} = \lim_{x\to 1} \frac{\left(\sqrt[3]{x}-1\right)\left(\sqrt {1+x} +\sqrt {2x}\right)}{1-x} =</math>
<math> = \lim_{x\to 1} \frac{-\left(1-\sqrt[3]{x}\right)\left(\sqrt {1+x} +\sqrt {2x}\right)}{\left(1-\sqrt[3]{x}\right)\left(1+\sqrt[3]{x}+\sqrt[3]{x^2}\right)} = \lim_{x\to 1} \frac{-\left(\sqrt {1+x} +\sqrt {2x}\right)}{1+\sqrt[3]{x}+\sqrt[3]{x^2}} =</math>
<math> = \frac{-\left(\sqrt {1+1} +\sqrt {2\cdot 1}\right)}{1+\sqrt[3]{1}+\sqrt[3]{1^2}} = \frac{-\left(\sqrt {2} +\sqrt {2}\right)}{1+1+1} =-\frac{2\sqrt{2}}{3}</math>